Endometrial ossification: A rare occurrence with review of literature - Sinha, Ruchi; Jamal, Iffat; -, Shuchismita (Indian Journal of Case Reports, 2020)
Endometrial ossification is a rare occurrence seen in reproductive age group. Patients usually present with complaints of menorrhagia and secondary infertility. We report a case of endometrial ossification in a 28-year-old female who presented with abdominal pain and menorrhagia. On transvaginal ultrasonography, a hyperechoic area within the uterine cavity, suggestive of an intrauterine foreign body was noted. Histopathological examination of the endometrial curettage showed bony spicules with chronic inflammatory cell infiltration.